257. Outcomes in Fungal Prosthetic Joint Infection. (4th December 2021) - Hollingshead, Caitlyn M; Duggan, Joan; Redfern, Roberta; Georgiadis, Gregory; Tank, Jason
Abstract: Background: There is a paucity of data in the literature regarding the most effective treatment and related outcomes of fungal prosthetic joint infection. The majority of reported cases are treated using a two stage revision method in which the initial prosthesis is removed and the patient is treated with systemic antifungal medications and potentially irrigation of the joint cavity with antifungal and antibacterial agents. Alternately, others have suggested a one-stage revision in order to prevent a period of significant functional impairment and potentially improved functional outcomes and lower overall costs. Cases of radical removal of the prosthesis without replacement have been reported. To date, the largest studies of total hip arthroplasty and total knee arthroplasty have included 37 and 45 patients, respectively. Methods: A retrospective record review of patients admitted within two health systems between January 1, 2007 and December 31, 2018 with prosthetic joints and a deep culture of the joint positive for fungal organisms was performed. Results: Eighteen patients fit criteria. Nine patients had knee replacements and nine patients had hip replacements. The average age at time of infection was 61. Ten patients were female. Average BMI was 32.1. Twelve presented with a painful joint, eight presented with drainage, and one with dehiscence. Average WBC count was 9.3, average ESR was 47, and average CRP was 11.8. All patients were noted with Candida species. Eight patients were treated with two stage revisions, three received one stage revisions as destination therapy. One required amputation. All but one patient was associated with concurrent bacterial infection. Of the twelve patients that had known outcomes, six were noted with cure and six were noted with relapse. All patients that were cured received two stage exchange or girdlestone procedure. Conclusion: In our study, fungal prosthetic joint infection was associated with poor outcomes. All of the patients in our study were noted with Candida species, which is in concordance with the known literature. Two stage exchange was associated with better outcomes. Disclosures: All Authors : No reported disclosures